2018
DOI: 10.1086/697170
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Metabolism and Cellular Stress Phenomena in the Gilthead Sea Bream (Sparus aurata)

Abstract: Seasonal temperature changes may take organisms to the upper and lower limit of their thermal range, with respective variations in their biochemical and metabolic profile. To elucidate these traits, we investigated metabolic and antioxidant patterns in tissues of sea bream Sparus aurata during seasonal acclimatization for 1 yr in the field. Metabolic patterns were assessed by determining lactate dehydrogenase, citrate synthase, and β-hydroxyacyl CoA dehydrogenase activities, their kinetic properties and plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 104 publications
3
20
0
Order By: Relevance
“…From our results it seems that the total amount of liver polyubiquitinated proteins, which are in the way to be drive to the proteasome degradation system, was not altered after 50 days of cold exposure. This result would be in agreement with those obtained from cultured sea bream during the cold season (Feidantsis et al 2018).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 2 more Smart Citations
“…From our results it seems that the total amount of liver polyubiquitinated proteins, which are in the way to be drive to the proteasome degradation system, was not altered after 50 days of cold exposure. This result would be in agreement with those obtained from cultured sea bream during the cold season (Feidantsis et al 2018).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…observed to change during ER with respect C. At the end of the recovery time, ubiquitin tagging of high-molecular-weight proteins reverted, but fewer low-molecular-weight proteins were still destined to be recycled. Meanwhile Feidantsis et al 2018, in a seasonal trial in cages, reported a gradual increase of total ubiquitin conjugates from April to June in heart and liver due to increased metabolic activity. Again, more studies will be necessary to understand better the specific pattern of polyubiquitination with respect to protein molecular weight.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential causal chain from temperature through metabolism and ROS production to telomere erosion, ectotherm telomere dynamics should be particularly affected by climatic effects during the time of year when lizards are active and bask to elevate their body temperature 9,17,33 . Our results thus agree with our prediction that a higher temperature during activity would result in telomere attrition and are in agreement with some, but not all, studies.…”
Section: Discussionmentioning
confidence: 99%
“…During summer, reptiles experience a spike in metabolism on a daily basis, due to temperature shifts, which should result in oxidative stress when anti-oxidation is non-perfect 25,[32][33][34] and telomere erosion is expected to increase unless balanced by telomerase 35,36 . In contrast, in winter a reptile's activity is low due to low temperature and thus metabolism and oxidative stress should be correspondingly lower 4,33 . Similarly, weather variation between years could result in variation in activity patterns and metabolic rate and thus potentially alter telomere dynamics.…”
mentioning
confidence: 99%